Covid-19 pandemic: an unconventional social media. A way to solve unresolved health issues? - Armocida, Emanuele; Martini, Mariano; Bussolati, Ovidio; Simonetti, Omar (Acta Biomedica Atenei Parmensis, 2024)
Over the last decade, social media has come to influence human lives in an unprecedented manner and have played a leading role in the Covid-19 pandemic. On one hand, social media has increased the degree of clarity and democracy in sharing scientific data on Covid-19; on the other hand, it has mined democracy by increasing the credibility of personal opinions. Mass media and social media refer to a diverse array of media technologies that reach a large audience via mass communication. It is our opinion that the Covid-19 pandemic itself should be considered a form of social media. As a matter of fact, conventional media has taken advantage of this unexpected and not-developed media to expand their capacity of distribution. The name we propose for this new media is pandemic media; a strong media capable to reach the largest audience and promote unresolved health issues, like the importance of washing hands, the need to get vaccinated, the fight against presenteeism, the usefulness of telemedicine.